Anti-β2GPI/β2GPI complex promotes thrombosis by activating the P2Y2/MAPKs pathway to increase human neutrophil peptides - Xin Guan; Wen Liu; Tianfeng Gao; Wenying Jin; Yueqiu Gao; Huiyuan Tan; Lujie Guo; Yanfen Zhang (PLoS ONE, 2025)
Anti-β2 glycoprotein I (Anti-β2GPI) antibodies are a heterogeneous group of antiphospholipid antibodies targeting β2 glycoprotein I (β2GPI). High titer of anti-β2GPI antibodies is a risk factor for thrombosis in antiphospholipid syndrome (APS). Although it has been shown that anti-β2GPI antibodies can induce neutrophil activation involved in thrombosis, the underlying mechanism remains unclear. In this study, we analyzed the clinical data of thrombotic patients who were positive or negative for anti-β2GPI antibodies, as well as healthy individuals. The results showed that the percentage and absolute count of neutrophils, serum levels of human neutrophil peptides (HNPs), and HNP mRNA levels were significantly higher in the anti-β2GPI-positive patient group compared to the healthy control group. Notably, when compared to the anti-β2GPI-negative patient group with similar neutrophil percentages and counts, the serum HNPs levels were also significantly elevated in the anti-β2GPI-positive patient group. In vitro, we further showed that anti-β2GPI and β2GPⅠ complex (anti-β2GPI/ β2GPⅠ complex) induced a concentration - and time-dependent increase in HNPs, which was mediated through P2Y2 receptors on the surface of neutrophils. Meanwhile, we found that intracellular signaling pathways P38MAPK (P38 mitogen-activated protein kinase) and ERK (extracellular signal-regulated kinase) were also involved in the generation of HNPs. We also found that high levels of human neutrophil peptide-1 (HNP-1) could induce the production of procoagulant factors von Willebrand factor (vWF) and P-selectin in endothelial cells through the nuclear factor-κB (NF-κB) signaling pathway, which increased the risk of thrombosis.